Values in nature - Rolston, Holmes, 1932-2025, author; Environmental Philosophy, Inc., publisher (Colorado State University. Libraries, 1981)
Nature is examined as a carrier of values. Despite problems of subjectivity and objectivity in value assignments, values are actualized in human relationships with nature, sometimes by (human) constructive activity depending on a natural support, sometimes by a sensitive, if an interpretive, appreciation of the characteristics of natural objects. Ten areas of values associated with nature are recognized: (1) economic value, (2) life support value, (3) recreational value, (4) scientific value, (5) aesthetic value, (6) life value, (7) diversity and unity values, (8) stability and spontaneity values, (9) dialectical value, and (10) sacramental value. Each is analyzed and illustrated with particular reference to the objective precursors of value as these are described by natural science.
Keywords: valuational education; value in nature; valuation; wilderness